The persisting environmental problem of disposal of expired and unused medicines - Abin Mani; Vijay Thawani (Wolters Kluwer Medknow Publications, 2019)
India continues to have the persisting environmental problem of disposal of expired, unused, unwanted medicines. Since this has not been studied well, the exact repercussions, therefore, are not hitherto known fully. There are no laws in country worthy of handling this problem. The municipal corporations handling the waste have not been sensitized to it. The media are insensitive to it, and populations are disorganized to take up the issue. Hence, the environment continues to suffer and will end with higher complication of human life and environment.